2013
DOI: 10.2174/1874155x01307010098
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Energy Performance of an Air Vortex Tube when the Inlet Parameters are Varied

Abstract: Abstract:The paper presents the analysis of the energy performance of an air vortex cooling tube under variations of the air inlet properties, with three independent experimental tests validated through the energy balance in the device.The experimental analysis includes the following variations of the input conditions: First, the effect of the air inlet pressure to the vortex tube, focused on the analysis of temperature variations in the output cold stream and in the cooling capacity when the cold flow fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, it can observe that temperature drop increases with the increase of inlet pressure. [28][29][30] In addition, it was found that maximum temperature drop is attained in the same range at all considered pressure input. 28,29 There takes place signi¯cant improvement of maximum temperature drop from a pressure 2 to 3 bar.…”
Section: 5mentioning
confidence: 73%
“…In addition, it can observe that temperature drop increases with the increase of inlet pressure. [28][29][30] In addition, it was found that maximum temperature drop is attained in the same range at all considered pressure input. 28,29 There takes place signi¯cant improvement of maximum temperature drop from a pressure 2 to 3 bar.…”
Section: 5mentioning
confidence: 73%
“…According to the results of the study the maximum energy separation was around 4 nozzles. Torrella et al [39] have studied on the energy performance of vortex tube under variations of the air inlet properties such as pressure and temperature with and without insulation conditions. They have concluded that the insulation does not modify appreciably the energy of performance of the vortex tube.…”
Section: Introductionmentioning
confidence: 99%
“…Through the results they concluded that vortex tube with length to diameter ratio of 20.5 and effective cold mass fraction 0.2 gives the best performance for designed tube from cooling point of view.Yunpeng Xue [34] did thermodynamic analysis on separation of energy inside the vortex tube and stated that Adiabatic expansion is found has the great capability to generate the temperature drop, and hence is considered as a main factor in the temperature separation within a vortex tube.Waraporn Rattanongphisat [35] implemented an thermoelectric module to extract heat from the external surface of hot tube and there by achieved an improvement of cooling efficiency of the vortex tube by 9.6%.S.S.Mohanty [36] carried experimental research to study the performance of vortex tube by varying nozzle number along with cold fraction.Xue [37] has gone through the analytical analysis of separation mechanism inside the vortex tube and finally stated that the isentropic expansion is taking place inside the tube.Mahar Kargaran [38] carried an experimental work on the effect of geometrical length and thermo physical properties on vortex tube performance. They concluded that cold temperature decreases with increase of inlet pressure and found a maximum temperature drop of 8 0 C.E.Torella [39] carried an experimental study on the performance of the vortex tube by varying inlet pressure and also by providing insulation. Also the effect of inlet air temperature was studied.…”
Section: Introductionmentioning
confidence: 99%